2016
DOI: 10.1002/mbo3.416
|View full text |Cite
|
Sign up to set email alerts
|

The Rhodococcus equi virulence protein VapA disrupts endolysosome function and stimulates lysosome biogenesis

Abstract: Rhodococcus equi (R. equi) is an important pulmonary pathogen in foals that often leads to the death of the horse. The bacterium harbors a virulence plasmid that encodes numerous virulence‐associated proteins (Vaps) including VapA that is essential for intracellular survival inside macrophages. However, little is known about the precise function of VapA. Here, we demonstrate that VapA causes perturbation to late endocytic organelles with swollen endolysosome organelles having reduced Cathepsin B activity and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…They were only in some cases strongly stained with LT ( Figure S2) whereas NRK lysosomes were always LT positive. In summary, VapA raises the pH in mouse macrophage lysosomes strongly whereas it does not in rat epithelial cell lysosomes, which is a possible reason for R. equi barely multiplying in NRK cells (Rofe et al, 2017).…”
Section: Lysosomes In Cells Incubated In Presence Ofmentioning
confidence: 86%
See 2 more Smart Citations
“…They were only in some cases strongly stained with LT ( Figure S2) whereas NRK lysosomes were always LT positive. In summary, VapA raises the pH in mouse macrophage lysosomes strongly whereas it does not in rat epithelial cell lysosomes, which is a possible reason for R. equi barely multiplying in NRK cells (Rofe et al, 2017).…”
Section: Lysosomes In Cells Incubated In Presence Ofmentioning
confidence: 86%
“…(a) RAW264.7 macrophages were infected for 2 or 24 hr with the virulent, VapA-producing strain R. equi 103+ or with VapA-lacking strains 103− or ΔvapA. In summary, VapA raises the pH in mouse macrophage lysosomes strongly whereas it does not in rat epithelial cell lysosomes, which is a possible reason for R. equi barely multiplying in NRK cells (Rofe et al, 2017). Lysosomes were fluorescently labelled with 10 kDa dark red fluorescent dextran using a pulse-chase protocol.…”
Section: Vapa Raises Lysosome Phmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting RCVs possess some late endocytic markers, such as Rab7, BMP, LAMP 1 and 2, but acquire neither cathepsin D nor v-ATPase. Recently, it was reported that VapA was taken into endocytic compartments when it was added to the culture media, and that cells fed VapA formed swollen endolysosome organelles with reduced activity of cathepsin B and accumulation of LBPA, LC3 and Lab7 [ 10 ]. Here, we show that the extracellular addition of VapA can exert an influence on the growth of intraphagocytic R. equi .…”
mentioning
confidence: 99%
“…Rofe et al . reported that the extracellular addition of VapA resulted in the formation of swollen endolysosome organelles with reduced cathepsin B activity and accumulation of late endocytic markers such as LBPA and Lab7, suggesting the loss of functional endolysosomes [ 10 ]. These features are similar to those found in RCVs [ 4 ].…”
mentioning
confidence: 99%